KAPASITAS VEKTOR DAN LAJU INOKULASI ENTOMOLOGIS An.peditaeniatus DAN An.sundaicus DI DESA SUNGAI NYAMUK, KABUPATEN NUNUKAN, KALIMANTAN UTARA - Sugiarto Sugiarto; Upik Kesumawati Hadi; Susi Soviana; Lukman Hakim (SPIRAKEL, 2017)
The intensity of malaria parasite transmission is normally expressed as the vectorial capacity and entomologic inoculation rate (EIR). Entomologic studies were conducted in Sungai Nyamuk Village to investigate the patterns of malaria transmission. Our study aimed to determine the vectorial capacity and entomological inoculation rate of An. peditaeniatus and An. sundaicus in endemic regions in Sungai Nyamuk Village, North Kalimantan. Mosquito collections were conducted for 18 months between August 2010 and January 2012. Mosquitoes were captured using human landing collections. A total of 5103 Anopheles mosquitoes comprising 11 species were caught and 2259 adult parous females were tested by ELISA for Plasmodium antigen. Of these, only one An. peditaeniatus (1.92%, n=52) and one An. sundaicus (0.29%, n=347) that originated from outdoor biting catch tested positive for P. falciparum circum sporozoite protein (CSP). The interval vector capacity of An. peditaeniatus (0.002-0.010) and An. sundaicus (0.010-0.069). The entomological inoculation rate of An. peditaeniatus and An. sundaicus =0.08 (~28 infective bites/person/ year). Our study concluded that transmission of P. falciparum malaria was occurring at Sungai Nyamuk Village. This research also showed that malaria transmission in Sungai Nyamuk Village occurred outdoors. Intensification of integrated vector management (IVM) of the participatory active community and vector control of outdoors Anophelines density needs to be done in success to malaria elimination.